Effects of oral intake fruit or fruit extract on skin aging in healthy adults: a systematic review and Meta-analysis of randomized controlled trials - Li, Haoying; Wang, Lu; Feng, Jinhong; Jiang, Lijuan; Wu, Jingping (Frontiers in Nutrition, 2023)
Background: In recent years, oral various fruits or supplements of fruits natural extracts have been reported to have significant anti-aging effects on the skin[1, 2],However, despite many studies on this topic, there is often no clear evidence to support their efficacy and safety. In this paper, we present a comprehensive review and Meta-analysis of the evidence for the safety and efficacy of oral fruits and fruits extracts in improving skin aging.Methods: Four databases, Pubmed, Embase, Web of Science, and Cochrane Library(CENTRAL), were searched for relevant literature from 2000-01 to 2023-03. Seven randomized controlled trials (RCTs) of fruit intake or fruit extracts associated with anti-skin aging were screened for Meta-analysis.Results: Compared to placebo, oral intake of fruit or fruit extracts showed significant statistical differences in skin hydration and transepidermal water loss (TEWL), with a significant improvement in skin hydration and a significant decrease in TEWL. No significant statistical difference was observed in minimal erythema dose (MED), overall skin elasticity (R2), or wrinkle depth, and no evidence of significant improvement in skin condition was observed.Conclusion: Meta-analysis results suggest that consume administration of fruits or fruit extracts significantly enhances skin hydration and reduces transcutaneous water loss, but there is insufficient evidence to support other outcome recommendations, including minimal erythema dose (MED), overall skin elasticity(R2), and wrinkle depth.